A new direct viscous-inviscid interaction method for aerodynamics analysis - Che Mohd Husin, Mohd Faizal (2018)
In manner the way how to solve the flow problem past through a streamlined body such as airfoil, the present work introduce the combination of the method for solving the Euler equation and the method for solving the boundary layers equation. Such approach is known as the direct viscous–inviscid interaction (DVII) method. The Euler equation is solved by use of finite volume method based on Roe‟s cell center Scheme while the Boundary layer equation is solved by use of the Keller Box method. Firstly the flow problem is solved which the whole flow domain is governed by the Euler equation. As the pressure distribution as the result of Euler solver obtained, then, it used as input for solving boundary layer equation according the Keller Box Scheme. The boundary layer solution beside provide the skin friction distribution along the body surface is also providing the boundary layer displacement thickness δ*. This quantity describes the displacement of stream line due to the viscous effects. Through displacement thickness, modifying geometry is carried out, to allow recalculation by using Euler solver can be done. As the pressure distribution based on new geometry is obtained, and then it is used for solving the boundary layer equation. This calculation is carried out for several times until a prescribed convergence criterion is fulfilled. The computer code based on these two approaches are developed and used for airfoil aerodynamics analysis. Comparison result between the developed computer code with the available experimental result and XFoil software for the case of flow past through airfoil NACA 0012 and RAE 2822 at various flow condition confirm that the present computer code had been developed successfully. Finally, present study found that the DVII method is only compatible for low and medium Mach number, M ≤ 0.8, where at higher Mach number, DVII method is breakdown due to solution not converge in inviscid solution. However, the convergence determination of global iteration should be included in current study in order to systemize entire computation and it is highly recommended for future.